Year level III community-oriented medical education (COME) program community orientation hours ? a summative evaluation - Inocencio, Froilan P. (1999)
UP College of Medicine, is introducing a new program - The COME program which aims to provide early, sustained prolonged immersion of the students in the community. This study is a descriptive evaluation which focuses on the Year Level III Program consisting of community learning activities to develop in the learner community awareness, as enumerated in the objectives. The program was implemented on the Academic Year 1998-1999, UPCM (Batch 2003). Since the start, a built-in evaluation plan has been incorporated containing faculty and students questionnaires and reflection papers. The plan attempts to look on these objectives and the process of the program. It also includes analysis of program strengths and weaknesses and recommendations for future modifications. The design is mainly descriptive and qualitative. It also employs document (content) analysis of the narrative responses. The framework is based on the Stake's model. The results of the study were and categorized prior to analysis. Data were analyzed according to their relationship with respect to their position in the program description matrix and in terms of congruence (symmetry and agreement between what is intended and what is observed). There is good evidence that the objectives of the Year Level III program have been attained. Both faculty and students are in agreement that the community learning activities are adequate enough in developing their community awareness". They also reiterated that the program is essential in the achievement of the Vision - Mission goal of the college which highlights community-orientation. One perceived strength is the timeliness of the program as it answers the global call and the realization that the goal of medical education is to address the health needs of the community. Program weaknesses were divided into three, namely, problems in faculty recruitment, duplication of course contents with FCH and problems arising from implementing COME in a traditional medical curriculum. There are no significant unintended effects noted in the program. The summary of the recommendations are enumerated: 1) Better logistic support from the administration; 2) Review of the components of the COME curriculum by the course coordinators; 3) Streamlining of evaluation tools by the evaluators; 4) Total reorientation of the faculty regarding the mission of the college; 5) Awareness of own personal development along community-orientation for the students; 6) Integration of the COME curriculum as the college gears toward Problem-Based Learning.
Special project (Master in Health Professions Education)--University of the Philippines Manila
Keywords: Community health services -- Study and teaching; Community medicine